Industrial training report: TAJ International College / Mohamad Fazari Harrun - Harrun, Mohamad Fazari (Universiti Teknologi MARA, Perlis, Faculty of Business and Management, 2021)
As a part being of Universiti Teknologi MARA’s undergraduate bachelor’s degree in finance program and last semester student, it is required to do an industrial training at the organization of their selection and are also required to do SWOT analysis the company itself in industry of their choosing to complete their studies. I am fortunate because managed to get an industrial that related to education sector, which is a IPTS and learn about the company SWOT. The company that I began the training are TAJ International College. TAJ International College were IPTS organization and offering high level education such as Diploma. The founder of TAJ International College was Dato’ Seri Hj. Tajuddin bin Abdul Rahman in 1996. In 2006 until present it was pass down to his daughter Tina Binti Dato’ Seri Hj. Tajuddin and the current director was Ahmad Abdullah Al Amin Aurani. I also was fortunate enough to be a part not only Finance Department, sometimes part of other department such as Marketing, IT and other. For this industrial training report, a study was conducted to identify the Strength, Weakness, Opportunity, and Threat (SWOT) and identify the aspect of it. The sample and research used for this study were Company performance such as company budgeting, projection cost, company environment, facility, and another factor. The result of the study will be shows in the Strength, Weakness, Opportunity, and Threat (SWOT) and since this study are not covered by any individual such as researcher, academic or the company, it was recommended that if future researcher and academic to widen the view study in the education sector. To conclude the study, this research about TAJ International College of Strength, Weakness, Opportunity, and Threat (SWOT) and the vital key of the management of the company. The further studies in this topic will be made in detail